Optimal Power Flow of Multiple Energy Carriers - Geidl, M.; Andersson, G. (IEEE transactions on power systems, 2007)
This paper presents an approach for combined optimization of coupled power flows of different energy infrastructures such as electricity, gas, and district heating systems. A steady state power flow model is presented that includes conversion and transmission of an arbitrary number of energy carriers. The couplings between the different infrastructures are explicitly taken into account based on the new concept of energy hubs. With this model, combined economic dispatch and optimal power flow problems are stated covering transmission and conversion of energy. A general optimality condition for optimal dispatch of multiple energy carriers is derived, and the approach is compared with the standard method used for electrical power systems. Finally, the developed tools are demonstrated in examples